2017
DOI: 10.3389/fimmu.2017.01662
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Lipids with Mincle: Structure and Function

Abstract: Mincle is a C-type lectin receptor that has emerged as an important player in innate immunity through its capacity to recognize a wide range of lipidic species derived from damaged/altered self and foreign microorganisms. Self-ligands include sterols (e.g., cholesterol), and β-glucosylceramides, and the protein SAP130, which is released upon cell death. Foreign lipids comprise those from both microbial pathogens and commensals and include glycerol, glucose and trehalose mycolates, and glycosyl diglycerides. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 75 publications
(119 reference statements)
0
51
0
Order By: Relevance
“… 32 34 The activation of Mincle results in downstream expression of cytokines, chemokines, and growth factors and leads to recruitment of inflammatory cells to the site of activation as a central part of the innate immune response to Mtb . 33 Several other Mtb cell wall glycolipids have been identified as Mincle activators, 34 , 35 and there is growing interest in using these Mincle ligands for the development of novel vaccine adjuvants. 36 …”
Section: Introductionmentioning
confidence: 99%
“… 32 34 The activation of Mincle results in downstream expression of cytokines, chemokines, and growth factors and leads to recruitment of inflammatory cells to the site of activation as a central part of the innate immune response to Mtb . 33 Several other Mtb cell wall glycolipids have been identified as Mincle activators, 34 , 35 and there is growing interest in using these Mincle ligands for the development of novel vaccine adjuvants. 36 …”
Section: Introductionmentioning
confidence: 99%
“…In a similar manner, Mincle suppresses Th17 immune responses, which as well have been suggested in coronavirus immunopathology and vaccine-induced immune enhancement ( 213 , 214 ). It was only recently discovered that activation of the Mincle receptor is a key activation pathway for Complete Freund’s Adjuvant (CFA), the “gold standard” adjuvant for eliciting cell-mediated immunity (CMI) in research models ( 215 217 ).…”
Section: Trained Immunity Utility For Vaccinesmentioning
confidence: 99%
“…Dectin-2 is a type II transmembrane protein with a short cytoplasmic tail and its extracellular domain is responsible for ligand binding. Like that of Dectin-2, Mincle-dependent signaling also occurs via FcRγ culminating in a pathway involving Syk and the CARD9–Bcl-10–MALT1 complex to activate NF-κB, which then leads to several pro-inflammatory responses and adaptive immune responses against pathogens [43, 44].…”
Section: Structure and Activation Of Clrsmentioning
confidence: 99%
“…These clues indicate that we may pay more attention to the possible relationship between Mincle and the pathogenesis of IBD [60]. Furthermore, Mincle can recognize various lipid components released from both host cells and microorganisms released upon cell death [44, 61]. In relation to Dectin-3, we found that the development of dextran sulfate sodium (DSS)-induced colitis can be promoted by Dectin-3 deficiency in mouse models challenged with Candida tropicalis [46], supporting its role in fungal recognition in the gut.…”
Section: Clrs-mediated Immune Recognition Of the Gut Microbiotamentioning
confidence: 99%